The Soft Power Strategy in the American Foreign Policy Towards Armenia - Gevorgyan, Nora (YSU Journal of International Affairs, 2024)
In today’s era of globalization and growing multiculturalism, the power of persuasion has a significant impact on enhancing understanding among nations and societies.In modern times soft power is increasingly being used as one of the main tools for shaping the foreign policy strategy of contemporary actors of world politics, in particular global powers. The article analyzes United States soft power and its implementation in the Republic of Armenia. The primary purpose of the study is to identify the key directions and examine the main operating mechanisms and tools of the US soft power in Armenia.The paper argues thatthe central objectives of the US soft power strategy in Armeniaare aimed at promoting the culture of Western liberalism and democracy in Armenia, as well as enhancing cooperation and mutual understanding between the two societies and states. The US soft power in relation to Armenia is mainly realized through educational instruments and relations, as well as cultural, public and civil diplomacy. The presence of various American agencies and funds, non-governmental foundations and organizations in Armenia contributes to the expansion and strengthening of American soft power in Armenia.
Keywords: soft power; foreign policy; the United States; Republic of Armenia; advancement of influence; non-coercive means